Molecular Dynamics Simulation of Thermal Properties of Ag3SI - Oztek, H. O.; Kavanoz, H. B.; Akdere, U.; Yilmaz, M.; Tasseven, C. (AMER INST PHYSICS, 2009)
A molecular dynamics (MD) simulation of Ag3SI in contrast pressure and temperature ensemble (NPT) is presented. Interionic interactions were modeled by Vashista-Rahman (VR) type potential which has been used in literature to study structural and transport properties and transition to superionic phase This research complements the previous studies by including the temperature evaluation of different elastic properties such as lattice parameter, specific heat, bulk modulus etc.
Keywords: Ag3SI; NPT; NVE; Vashista-Rahman; lattice parameter; bulk modulus; specific heat; Physics